ANALISIS PENERAPAN SISTEM MANAJEMAN KESELAMATAN DAN KESEHATAN KERJA (SMK3) DI PT. WIKA BK KSO PROJECT BENDUNGAN LAUSIMEME KABUPATEN DELI SERDANG TAHUN 2023 - Ginting, Evfy Septriani (Jurnal Kajian Kesehatan Masyarakat, 2023)
According to NIOSH construction is one of the most dangerous jobs in the world, resulting in the highest death rate of any sector. The risk of falling is the highest cause of accidents. The Employment Social Security Administration Agency (BPJS) throughout 2018 recorded 157,313 work accident cases that occurred in Indonesia. Therefore, the government as state organizers has an obligation to provide protection to workers. This is realized by the government with the issuance of regulations such as RI Law no. 1 of 1970 concerning work safety, and Government Regulation No. 50 of 2012 concerning the Occupational Safety and Health Management System (SMK3). The purpose of this research is to analyze how the implementation of SMK3 in PT. WIKA BK KSO Lausimeme Dam Project, Deli Serdang Regency, in 2023. The research design uses a mixed methods research method between quantitative methods and qualitative methods to be used together. Research informants as many as 4 people. The results of this study obtained the Implementation of Policy, Planning, Implementation of Performance Monitoring and Evaluation Plans and Reviewing and Improving the Performance of the Occupational Safety and Health Management System at PT. WIKA BK KSO The Lausimeme Dam Project has been fulfilled or implemented, it's just that the implementation of the SMK3 has not gone according to target. The conclusion in this study is the level of implementation of the Occupational Safety and Health Management System (SMK3) at PT. WIKA BK KSO Lausimeme Project is the achievement of (GOOD) implementation with a percentage of 71% conforming implementation and 29% non-compliance findings.